Real-time stress detection and monitoring system using IoT-based physiological signals - Atika Hendryani; Dadang Gunawan; Mia Rizkinia; Rinda Nur Hidayati; Frisa Yugi Hermawan (Bulletin of Electrical Engineering and Informatics, 2023)
Currently, medical experts use psychophysiological questionnaires to evaluate human stress levels during counseling or interviews. Typically, biochemical samples use urine, saliva, and blood samples to identify the effects of stress on the human body. This research explains that stress detection can be done by analyzing psychological signals and the importance of monitoring stress levels. The authors develop research on stress detection based on psychological signals. The system then processes the recorded data; the android application displays the calculation results. The database can also be accessed as a spreadsheet via a web application. The design of real-time stress detection and monitoring using internet of things (IoT) can work well.